A new hybrid explicit/implicit in-plane-out-of-plane separated representation for the solution of dynamic problems defined in plate-like domains. (November 2018) - Quaranta, G.; Bognet, B.; Ibañez, R.; Tramecon, A.; Haug, E.; Chinesta, F.
Highlights: In-plane-out-of-plane separated representations are extended to dynamics. We propose an hybrid implicit (thickness)/explicit (in plane) time integration. Explicit 2D plate and shell are enriched (3D) without impacting stability. Abstract: The present paper extends in-plane-out-of-plane separated representations successfully used for addressing fully 3D model solutions defined in plate-like domain, to dynamics. Common time integration are performed using explicit or implicit strategies. Even if the implementation of implicit integration schemes into a 3D in-plane-out-of-plane separated representation does not imply major difficulties, the use of explicit integration preferable in many applications becomes a tricky issue. In fact the mesh employed for discretizing the out-of-plane dimension (thickness) determines the maximum time-step ensuring stability. In this paper we introduce a new efficient hybrid explicit/implicit in-plane-out-of-plane separated representation for dynamic problems defined in plate-like domains that allows computing 3D solutions with the stability constraint exclusively determined by the coarser in-plane discretization.